2022
DOI: 10.26434/chemrxiv-2022-kngl7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of structure and dynamics of cardiac troponin by phosphorylation and mutations revealed by molecular dynamics simulations

Abstract: Phosphorylation of cardiac muscle troponin I by protein kinase A enhances troponin regulatory dynamics and is an essential part of the’ flight or fight’ response to adrenaline. Elucidating how phosphorylation at serines 22 and 23 modulates structural dynamics has been difficult as key regulatory segments of troponin are unresolved. The effect of phosphorylation on the wild type, obtained from all-atom molecular dynamics simulations of the troponin core, demonstrates a significant rigidification of the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In the case of DCM mutations a case can be made that this is causative of the disease since it is the only mutation-related property that is common to every thin-filament related DCM mutation ( 1 , 33 , 38 ), whereas for HCM, the increase in Ca 2+ -sensitivity is probably the key driver of the cardiomyopathy. Mechanistically, uncoupling usually involves an impaired response of the thin filaments to TnI phosphorylation ( 34 ), however, the cTnI R21C mutation has a mechanism whereby the mutation interferes with the phosphorylation process itself ( 35 ). Another mechanism that could generate impaired lusitropy is if the balance of phosphorylation of TnI and PLB in response to Iso is disturbed as suggested by Najafi et al ( 36 ).…”
Section: Mutations Can Also Suppress Lusitropymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of DCM mutations a case can be made that this is causative of the disease since it is the only mutation-related property that is common to every thin-filament related DCM mutation ( 1 , 33 , 38 ), whereas for HCM, the increase in Ca 2+ -sensitivity is probably the key driver of the cardiomyopathy. Mechanistically, uncoupling usually involves an impaired response of the thin filaments to TnI phosphorylation ( 34 ), however, the cTnI R21C mutation has a mechanism whereby the mutation interferes with the phosphorylation process itself ( 35 ). Another mechanism that could generate impaired lusitropy is if the balance of phosphorylation of TnI and PLB in response to Iso is disturbed as suggested by Najafi et al ( 36 ).…”
Section: Mutations Can Also Suppress Lusitropymentioning
confidence: 99%
“…Studies on the effects of mutations that uncouple TnI phosphorylation from the Ca 2+ -sensitivity shift indicate that they probably act by inducing a subtle, phosphorylation-dependent change in the dynamics of troponin ( 69 74 ), most clearly indicated by a recent study on the TnC G159D mutation ( 34 ). Remarkably, it has been found that several small molecules are capable of fully restoring the Ca 2+ -sensitivity shift in vitro and restoring lusitropy to mutated cardiomyocytes ( 7 , 45 , 75 , 76 ).…”
Section: Restoration Of Lusitropy As a Potential Treatment For Cardio...mentioning
confidence: 99%
“…Molecular Dynamics studies 4.3.1 MD simulations of troponin were performed as described by Yang et al [24].…”
Section: 3mentioning
confidence: 99%
“…selected two of the phosphorylated residues in the MYH7 polypeptide (Ser1362 in RYR1‐CM and Tyr1375 in both RYR1‐CM and RYR1‐RM) for closer examination using molecular dynamics (MD) simulations. MD has been widely used to examine molecular processes that are challenging, if not impossible to assess in muscle with current experimental approaches 11,15–19 . Dynamic simulations of portions of MYH7 rod suggest that phosphorylation could negatively impact structural dynamics of the rod—and by implication the thick filament backbone and interaction with IHM—in myopathy patients.…”
Section: Figurementioning
confidence: 99%
“…MD has been widely used to examine molecular processes that are challenging, if not impossible to assess in muscle with current experimental approaches. 11,[15][16][17][18][19] Dynamic simulations of portions of MYH7 rod suggest that phosphorylation could negatively impact structural dynamics of the rod-and by implication the thick filament backbone and interaction with IHM-in myopathy patients.…”
Section: Ryanodine Receptor-associated Myopathies: What's Myosin Got ...mentioning
confidence: 99%